Didactics of written argumentation with Spanish as a Foreign Language (SFL) students at university level in Algeria - Baaziz, Saida; de Vicente-Yagüe Jara, María Isabel (Frontiers in Psychology, 2023)
The general objective of this research is to investigate the impact of a program focusing on the development of argumentation techniques on the improvement of critical essays by SFL students at the University of Algiers 2. A quasi-experimental pretest-posttest study was carried out, where the indicators of textual levels obtained by the students were evaluated and compared, both before and after a learning intervention. The study involved 126 students studying SFL at the University of Algiers 2, whose essays were analyzed using Parodi and Núñez’s (1999) analysis guidelines, in order to evaluate the students’ argumentative competence at the three levels of microstructure, macrostructure and superstructure. Once the results were analyzed, statistically significant differences were observed in the indicators of the macrostructure, and superstructure. Furthermore, an improvement in the post-test means is observed in the indicators of these microstructure. Lastly, the intervention program strengthened students’ argumentative abilities, which had a significant effect on their critical essays.